Sprawozdania sytuacyjne Urzędu Wojewódzkiego Śląskiego za lata 1933-1939 jako źródło do aktywności związków mniejszości niemieckiej w województwie śląskim - Bober, Sabina (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The coverage of the situation reports of the Silesian authorities for the period 1933-1939 highlighted the behaviour of German society involved in creating unions and associations of various shades and political options. This material depicts the picture with the evolution in the attitude of the Germans in Silesia going in two directions. One is marked with irredentism and deriving not only inspiration, but also directives and financial resources from the Weimar Republic and later the Reich. The other direction was more or less oriented towards the autonomous policy (in relation to the political objectives of the German policy) of the part of the minority, which required loyal inclusion in the Polish reality. The most often mentioned advocate of the latter direction was Dr Eduard Pant. The possibilities of following the same road were also in other groupings, especially Catholic ones. The situation changed as the Nazi regime began the road to war. In this case, the opposition to Hitler in German society actually was gradually dying; a majority of the Germans outside the Reich decided to follow Hitler as their patriotic duty, which did not have to mean they identified with the Nazi world-view.